Quarterly indicator of economic activity to intermediates citys. Case: Huancayo - Loayza-Acosta, Gustavo (2019)
In Peru, the availability of information on macroeconomic indicators is at the national aggregate level, information at the subnational level is scarce and often lags behind. This paper presents an econometric model that will allow to calculate economic activity at the subnational level, the resulting indicator is constructed under the principle of representativeness and in real terms, additionally, the non-primary indicators will be obtained through dissemination indexes, a methodology established by the Organization for Cooperation and Economic Development (OECD)